2023
DOI: 10.1002/ctm2.1179
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic analysis of metformin signaling in colorectal cancer cells elucidates mechanism of action and potential therapeutic opportunities

Abstract: Background The biguanide drug metformin is a safe and widely prescribed drug for type 2 diabetes. Interestingly, hundreds of clinical trials have been set to evaluate the potential role of metformin in the prevention and treatment of cancer including colorectal cancer (CRC). However, the “metformin signaling” remains controversial. Aims and Methods To interrogate cell signaling induced by metformin in CRC and explore the druggability of the metformin‐rewired phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 148 publications
0
18
0
Order By: Relevance
“…A very comprehensive study of metformin-regulated signalling in 10 different colorectal cancer cell lines has identified that the activity of more than 80 kinases and phosphatases form part of diverse signalling pathways that are regulated by metformin, across the 10 cell lines [ 24 ]. Direct changes to phosphorylation were demonstrated for more than 40 kinases and phosphatases in all cell lines ( figure 5 a , [ 24 ]).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A very comprehensive study of metformin-regulated signalling in 10 different colorectal cancer cell lines has identified that the activity of more than 80 kinases and phosphatases form part of diverse signalling pathways that are regulated by metformin, across the 10 cell lines [ 24 ]. Direct changes to phosphorylation were demonstrated for more than 40 kinases and phosphatases in all cell lines ( figure 5 a , [ 24 ]).…”
Section: Resultsmentioning
confidence: 99%
“…A very comprehensive study of metformin-regulated signalling in 10 different colorectal cancer cell lines has identified that the activity of more than 80 kinases and phosphatases form part of diverse signalling pathways that are regulated by metformin, across the 10 cell lines [ 24 ]. Direct changes to phosphorylation were demonstrated for more than 40 kinases and phosphatases in all cell lines ( figure 5 a , [ 24 ]). Similarly, several studies have investigated AMPK-dependent phosphorylation and over 180 AMPK-dependent substrates have been identified, including more than 15 kinases and phosphatases ( figure 5 a , [ 24 , 37 40 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations